Breastfeeding avoidance following psychological intimate partner violence during pregnancy: a cohort study and multivariate analysis - Martín-de-las-Heras, Stella; Velasco, C.; Luna-del-Castillo, Juan de Dios; Khan, Khalid Saeed (Wiley, 2019)
Objective To evaluate if the experience of psychological intimate partner violence (IPV) adversely affects breastfeeding rates. Design A cohort study. Setting Maternities in 15 public hospitals, drawn using cluster sampling of obstetric services in Andalusia, Spain. Population A total of 779 consecutive mothers receiving antenatal care including ultrasound and giving birth during February–June 2010. Methods Trained midwives gathered IPV data using the Index of Spouse Abuse validated in the Spanish language (score ranges: 0–100, higher scores reflect more severe IPV; cut‐off: psychological IPV = 25). Sociodemographic data including lack of kin support, and obstetric and neonatal outcomes were collected. Multivariate logistic regression estimated adjusted odds ratios (aOR), with 95% confidence intervals (CI), of the relationship between psychological IPV and breastfeeding, controlling for sociodemographic characteristics and obstetric complications. Main outcome measure Breastfeeding avoidance defined as lack of breastfeeding or pumping of breast milk to feed the new baby in the immediate post‐partum period. Results Response rate was 92.2%. A total of 70% (n = 545) of women initiated breastfeeding. Psychological IPV, reported by 21.0% (n = 151), increased the odds of breastfeeding avoidance (aOR = 2.0; 95% CI = 1.2–3.3) adjusting for the presence of obstetric complications (aOR = 1.6; 95% CI = 1.0–2.4). Conclusions Mothers with psychological IPV avoid breastfeeding. Clinicians should be aware of the risks to infant arising from this deficiency due to IPV in pregnancy.
Keywords: Vilencia de género; Madres - Aspectos psicológicos; Breastfeeding; Pregnancy; Risk factors; Gender-based violence; Intimate partner violence; Maternal outcomes